A novel functionally graded bilayer membrane with excellent barrier function and in vivo osteogenesis promotion for guided bone regeneration - Li, Junxuan; Ding, Jiaxin; Zhou, Tao; Li, Bolun; Wang, Jingjing; Wang, Hanchi; Fu, Li (Frontiers in Pharmacology, 2024)
Introduction Guided bone regeneration (GBR) technology has been widely used as a reliable method to address alveolar bone defects. To improve the clinical effects of GBR approach, there have been attempts to develop barrier membranes with enhanced regenerative properties. However, modifying the material and structure of GBR membranes to integrate physicochemical properties and biological activity remains challenging. The aim of this study was to develop a novel functionally graded bilayer membrane (FGBM) with a gradient structure and composition, and to evaluate its osteogenesis promotion effect for GBR. Methods By combining the phase inversion method and electrospinning method, functionally graded bilayer membranes (FGBM) with gradient structure and composition of poly(lactic-co-glycolic acid) (PLGA), nano-hydroxyapatite (nHA), and gelatin were fabricated in this study. The physicochemical and biological properties of the prepared FGBM, including structural and morphological characterization, mechanical properties, in vitro biodegradation, cell behaviors, and in vivo osteogenic bioactivity, were comprehensively evaluated. Results The findings demonstrated the successful fabrication of PLGA/nHA/gelatin FGBM with an asymmetric structure, exhibiting enhanced hydrophilic, mechanical, and degradation properties. The incorporation of gelatin not only improved the biological integration, but also enhanced the binding affinity between electrospun fiber layer and phase inversion layer. The FGBM with a 30% nHA mass fraction and a PLGA/gelatin mass ratio of 1:1 exhibited excellent barrier function and osteogenic bioactivities in vitro and in vivo. Discussion This work demonstrated the potential of PLGA/nHA/gelatin FGBM in bone regeneration and provided valuable insight for the development of barrier membrane.